Immunoproteomic mediators of diabetic peripheral neuropathy: causal insights from Mendelian randomization and single-cell validation - Hu, Chenhao; Sun, Shengqiao; Li, Dezhi; Yu, Lebao; Guo, Chao; Liu, Song (Frontiers in Immunology, 2026)
ObjectiveTo elucidate causal roles of circulating immune cells and plasma proteins in diabetic peripheral neuropathy (DPN) pathogenesis using integrative Mendelian randomization (MR) and single-cell validation.MethodsWe employed two-sample MR to assess causal effects of 731 immune traits and 4,719/2,923 plasma proteins on DPN risk (FinnGen: 2,843 cases/389,580 controls). Significant exposures underwent mediation MR to identify protein-immune interactions. Validation included scRNA-seq of sural nerves (4 DPN vs. 3 controls) and flow cytometry/immunofluorescence for dendritic cell infiltration.ResultsFive HLA-DR+ immune phenotypes (predominantly dendritic subsets) increased DPN risk (OR = 1.27–1.63, FDR<0.05). Six plasma proteins conferred protection (MICB, HLA-DRA, CAPS, CD79B, AGER, PRKCG; OR = 0.10–0.58). Mediation MR revealed pathogenic immune cells suppress CAPS/HLA-DRA expression (mediating 26.3% of neurotoxicity, P<0.001), while MICB attenuated DPN by inhibiting immune phenotypes. scRNA-seq confirmed conventional dendritic cell infiltration in DPN nerves and disrupted reparative crosstalk with Schwann cells.ConclusionWe establish a causal neuroimmune network wherein HLA-DR+ dendritic cells drive DPN through suppression of protective plasma proteins (CAPS/HLA-DRA), while MICB exerts dual protection. These findings reveal novel therapeutic targets for DPN intervention.